Inovasi dan Makna Batik Tradisional: Persfektif Mahasiswa FPSD UPI Bumi Siliwangi - Hayati, Ai Citra; Lasmanah, Dewi Isma; Ramadhani, Amalia; Putri, Ainunnisa Imelda; Putra, Tedi Sidik Gumilang (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
The aim of this research is to: 1) Explore the knowledge of FPSD UPI Bumi Siliwangi students about the meaning contained in the motifs of megamendung batik, kawung batik, seven-rupa batik, parang batik and sogan batik. 2) find out more about the innovations that students have for these batiks so that they can be maintained. The data obtained in this research is the result of observation, interviews and data collection based on the research focus. The results of this research show that 1) the known meaning of the batiks that have been mentioned. Researchers also deliberately chose batik which is mostly known by all groups. 2) the innovation that students have for batik is, among other things, their way of keeping batik maintained. This research explores the relationship between innovation and the meaning of traditional batik motifs in the context of a societal perspective through analyzing society and identifying patterns of behavior, beliefs and values that shape the meaning of batik behind the innovations received. So the results are focused on the importance of understanding the cultural and social context in developing relevant innovations so that they can provide new insights for product development, policy planning and positive innovation in social life.